The PROCAN-B study protocol: Early diagnosis of PROstate CANcer for Black men-a community-centred participatory approach in Scotland and the North-East of England. - Floor Christie-de Jong; Judith Eberhardt; Jonathan Ling; Marie Kotzur; Olugbenga Samuel Oyeniyi; Lawrence Nnyanzi; John Kabuye; Martin Kalemba; Kathryn A Robb (PLoS ONE)
Background Prostate cancer is the most common cancer in the UK and Black African-Caribbean men are twice as likely to develop prostate cancer as white men. These cancer inequalities need urgent tackling. Barriers to early diagnosis are complex and require complex solutions. Culturally-tailored, community-centred and participatory approaches show promise in tackling cancer inequalities. We aim to co-design a culturally appropriate intervention to tackle barriers to early diagnosis of prostate cancer for Black men in Scotland and the North-East of England using a community-centred participatory approach. Methods The PROCAN-B study is a mixed methods study set in Scotland and the North-East of England. A Public Involvement and Community Engagement (PICE) group (n = 12), is involved at every step of the research. Drawing on principles of the Integrated Screening Action model (I-SAM), the study has 8 objectives: 1) to explore barriers to early diagnosis of prostate cancer among Black men (45+) through focus groups (n = 12); 2) to co-design a culturally acceptable peer-led intervention to tackle barriers to early diagnosis of prostate cancer in Black men; 3) to train members of the community as 'peer-facilitators' (n = 8); 4) to deliver the intervention in each location, facilitated by peer-facilitators, with a purposive sample (n = 20) of Black men (45+); 5) to qualitatively evaluate the intervention through focus groups; 6) to refine the intervention based on qualitative feedback; 7) to pilot the refined intervention with another purposive sample (n = 40) through a cross-sectional survey pre- and post-intervention; 8) to qualitatively evaluate the refined intervention through focus groups to further refine the intervention. Discussion Community-centred and culturally tailored interventions have potential to be effective in addressing barriers to early diagnosis of prostate cancer, and thus ultimately reduce morbidity and mortality rates through earlier diagnosis in Black communities.